PEDAGOGICAL METHODS WHICH ARE IMPORTANT IN TEACHING FOREIGN LITERATURE ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2023)
The role of communication, including intercultural communication and literature, is increasing in modern human life. But in our relations with representatives of other nations, we inevitably proceed from the existing ideas (heterostereotypes) about them, one of the sources of which is fiction. Therefore, in order to understand (not always consciously) how inter-ethnic communication is built, it is important to explain the images of representatives of certain nationalities that are depicted in the field of artistic creation.